Cost and Time Performance Analysis Using the Earned Value Concept in the Construction of the Integrated Lecture Building at the State Polytechnic of Shipbuilding Surabaya - Bahari, Victor Fajar; Rizki, Muhammad Alvan (Journal La Multiapp, 2025)
Time and cost control is an important aspect in the success of construction projects, especially in large-scale projects such as the construction of the Integrated Lecture Building (GKT) of Surabaya State Polytechnic of Shipping. This research aims to analyze the time and cost performance of the project using the earned value concept. With this method, measurement and evaluation of project performance can be done quantitatively based on earned value data. The results of the analysis show that from the evaluation results in the 35th week, the value of ACWP is Rp. 47,741,219,980.93, the BCWP value is Rp. 47,874,478,839.55, and the BCWS value is Rp. 47,721,477,927.80. Based on the ACWP, BCWP, and BCWS values, the Cost Variance (CV) value is Rp. 133,258,858.63 and the Schedule Variance (SV) is Rp. 153,00,911.76. This figure indicates that the costs incurred are more efficient and the implementation time is faster than planned. The values of CPI and SPI equal to 1.00 indicate good cost performance within budget as well as good schedule performance with the schedule on time against the plan. The estimated cost of ETC is Rp. 1,476,532,576.73 and EAC is Rp. 49,217,752,557.66. The estimated time of ETS is Rp. 1.99 weeks and EAS is 36.99 weeks. With the application of this method, deviations from schedule and budget can be identified early so that decision making can be done appropriately to return the project to the predetermined schedule.